PERKEMBANGAN PERKEBUNAN DAN PELABUHAN Dl KARESIDENAN TEGAL1830-1990 (Development of Plantation and Harbour in legal Residency (1830-1900)) - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 2004)
ABSTRACT The aim of the research on this thesis is to reveal the development of plantation in Tegal residency and its effect on the development of harbour in Tegal during the year 1830-1900. In order to explain the correlation between the plantation activities in hinterland and the harbour in Tegal, this re¬search makes us of the economic and social approaches. The thesis writer uses various archieves as primary data and the books as secondary resources to get a comprehensive analysis.The result of the research shows that during the year 1830-1900, the crop of the hinterland plantation especially coffee and cane sugar in Tegal were abundant. This was because of the Dutch Colonial government policy if the intensive investment in these sectors. By the abundant product, there was symbiosis mutualism between hinterland as the supplier of the plantation product and the harbour as demand agent. The hinterland plantation supplied the export commodity and income tax for the harbour. This condition made community more dynamic and diversi¬fication of the efforts, therefore they did not focus on a certain agricultural sector. This mutual symbiosis connection was accelerated by building up the infrastructures such as roads, irrigations, means of transportations, ma¬chines, factories, markets etc. It was in accordance with the first aim, that was to get batig slot for colonial interest.